(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This thesis reviews prostate cancer screening methods, highlighting that systematic screening can reduce mortality by about 20%. Advanced tools like MRI-guided biopsy improve diagnosis and reduce unnecessary procedures. Combining personalized risk assessment with shared decision-making optimizes screening benefits while maintaining patient quality of life.